2008
DOI: 10.2105/ajph.2007.124271
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Conditions and Well-Being of Indigenous Farmworkers

Abstract: Increasing numbers of indigenous farmworkers from Mexico and Guatemala have been arriving in the Pacific Northwest (indigenous people are not of Hispanic or Latino descent and migrate from regions with unique cultural and linguistic traditions). Multilingual project outreach workers administered surveys to 150 farmworkers in Oregon to assess health, occupational safety, and general living conditions. This study confirms the increasing presence of indigenous peoples in Oregon and characterizes differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…The reason for this might be the fact that farmworkers find it very hard to find work in other sectors, as stated in another study. 18 In the present study, about half of the MSFs had a self reported chronic or acute disease. This might be explained by many reasons such as insufficient and imbalanced diet, unhealthy living quarters, lack of education, poverty, lack of responsibility for self-care and obstacles to transportation.…”
Section: Discussionmentioning
confidence: 52%
“…The reason for this might be the fact that farmworkers find it very hard to find work in other sectors, as stated in another study. 18 In the present study, about half of the MSFs had a self reported chronic or acute disease. This might be explained by many reasons such as insufficient and imbalanced diet, unhealthy living quarters, lack of education, poverty, lack of responsibility for self-care and obstacles to transportation.…”
Section: Discussionmentioning
confidence: 52%
“…Between April and October 2006, the indigenous community educator partners administered the baseline survey at labor camps, farmworker homes, and community centers. 6 The indigenous community educator partners administered the follow-up surveys between May and July 2008 at locations similar to those used for the baseline survey, in the Willamette Valley region of Oregon. Project partners then prerecorded the baseline and follow-up surveys in the Mixteco Alto, Mixteco Bajo, and Triqui (Copala) indigenous languages to ensure that survey questions were linguistically appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the orientation to research, several strong examples exist of CBPR with workers, including indigenous and Latino agricultural workers in Oregon, 56 hotel room cleaners in San Francisco and Las Vegas, Nevada, 57,58 and custodial workers in Iowa. 59 The Restaurant Opportunities Center also has been successful in organizing restaurant workers of diverse races and ethnicities for living wages and against wage theft in dozens of cities across the country.…”
Section: Reviewmentioning
confidence: 99%